Towards Web-based Delta Synchronization for Cloud Storage Services - Xiao, He; Li, Zhenhua; Zhai, Ennan; Xu, Tianyin; Li, Yang; Liu, Yunhao; Zhang, Quanlu; Liu, Yao (16th USENIX Conference on File and Storage Technologies (FAST 2018), 2018)
Delta synchronization (sync) is crucial for network-level efficiency of cloud storage services. Practical delta sync techniques are, however, only available for PC clients and mobile apps, but not web browsers—the most pervasive and OS-independent access method. To understand the obstacles of web-based delta sync, we implement a delta sync solution, WebRsync, using state-ofthe-art web techniques based on rsync, the de facto delta sync protocol for PC clients. Our measurements show that WebRsync severely suffers from the inefficiency of JavaScript execution inside web browsers, thus leading to frequent stagnation and even hanging. Given that the computation burden on the web browser mainly stems from data chunk search and comparison, we reverse the traditional delta sync approach by lifting all chunk search and comparison operations from the client side to the server side. Inevitably, this brings considerable computation overhead to the servers. Hence, we further leverage locality-aware chunk matching and lightweight checksum algorithms to reduce the overhead. The resulting solution, WebR2sync+, outpaces WebRsync by an order of magnitude, and is able to simultaneously support 6800–8500 web clients’ delta sync using a standard VM server instance based on a Dropbox-like system architecture.